Human immunodeficiency virus type-1 induces a regulatory B cell-like phenotype in vitro. Issue 10 (October 2018) - Lopez-Abente, Jacobo; Prieto-Sanchez, Adrián; Muñoz-Fernandez, Maria-Ángeles; Correa-Rocha, Rafael; Pion, Marjorie
Abstract Individuals infected with human immunodeficiency virus type-1 (HIV-1) usually show a general dysregulation and hyper-activation of the immune system. A direct influence of HIV-1 particles on B-cell phenotypes and functions has been previously described. However, the consequences of B-cell dysregulation are still poorly understood. We evaluated the phenotypic changes in primary B cells after direct contact with HIV-1 particles in comparison with different types of stimuli. The functionality of treated B cells was challenged in co-culture experiments with autologous CD4+ and CD8+ T cells. We demonstrated that HIV-1 induces a phenotypic change in B cells towards a regulatory B-cell phenotype, showing a higher level of IL-10, TGF-β1, EBI3 or IL-12(p35) mRNA expression and acquiring an immunosuppressive profile. The acquisition of a Breg phenotype was confirmed by co-culture experiments where HIV-treated B cells reduced the proliferation and the TNFα production of CD4+ or CD8+ T cells. This suppressive ability of HIV-treated B cells was dependent on cell-to-cell contact between these B cells and effector cells. To our knowledge, these data provide the first evidence that HIV-1 can directly induce a regulatory B cell-like immunosuppressive phenotype, which could have the ability to impair specific immune responses. This dysregulation could constitute one of the mechanisms underlying unsuccessful efforts to develop an efficient vaccine against HIV-1.